PENGARUH KEADILAN ORGANISASI DAN STRES TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) GURU SEKOLAH DASAR NEGERI DI KECAMATAN DUKUHWARU TEGAL, JAWA TENGAH - Halipah Halipah (Jurnal Manajemen Pendidikan, 2015)
The objective research is to obtain information concerning to the effect of organizational justice and stress toward teachers organizational citizenship behavior. The research was conducted by using survey method with path analysis in testing hypothesis. In this research, 92 from 120 teacher of teachers selected random sampling. The research was focused on tree aspect; organizational justice and stress toward teachers organizational citizenship behavior. The data were colected with questionnaire and analyzed with path analysis. Result on the analyisis it is conculaded that (1) there the positive direct effect of organizational justice towards organizational citizenship behavior, (2) there is negative direct effect of stress towards organizational citizenship behavior and (3) ) there is negative direct effect of organizational justice towards stress.